Analysis of 6-week mortality and influencing factors in patients with liver cirrhosis and portal vein thrombosis complicated by acute gastrointestinal bleeding - Junli Zhang; Ling Feng (PLoS ONE, 2026)
Objective To explore the 6-week mortality of acute gastrointestinal bleeding in patients with liver cirrhosis and portal vein thrombosis and to analyze its influencing factors. Methods This was a retrospective study. We retrospectively screened 232 patients with liver cirrhosis and portal vein thrombosis complicated by acute gastrointestinal bleeding who were admitted to West China Hospital of Sichuan University from January 1，2020 to November30，2022. Of the 232 patients, 75 had their first bleeding. Additionally, the patients were divided into a mortality group (n = 34) and a non-mortality group (n = 198) based on whether they died within 6 weeks of the onset of gastrointestinal bleeding. Baseline general information, laboratory indicators, and other clinical data of the two groups were compared, and the independent risk factors for 6-week mortality in patients with liver cirrhosis and portal vein thrombosis complicated by acute gastrointestinal bleeding were analyzed. Results There were significant differences between the two groups in terms of the etiology of liver cirrhosis, HCC, 5-day treatment failure rate (8.62%), TBiL, ALT, BUN, Na, eGFR, DBiL, AST, GGT, ALP, CR, WBC, PLT, and PT(p < 0.05). Multivariate logistic regression analysis revealed that elevated ALP levels showed a positive association with 6-week mortality [OR=1.01, 95% CI (1.01, 1.01), p < 0.01] and 5-day treatment failure showed a positive association with 6-week mortality [OR=11.27, 95% CI (3.45, 36.81),p < 0.01]. Conclusion Elevated ALP and 5-day treatment failure were found to be independent risk factors for 6-week mortality in patients with cirrhosis and portal vein thrombosis complicated by acute gastrointestinal bleeding.